EXPLOTAÇÃO DE ÁGUA SUBTERRÂNEA EM SÃO JOSÉ DOS CAMPOS - EFEITOS OBSERVADOS A LONGO TEMPO - FRANCO FILHO, FERNANDO WILLI BASTOS; DE SOUZA, JOÃO CARLOS SIMANKE (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL